Japan's Inclusive Development: The Strategy and Policies of The Japanese Government Towards Disability Education. - Ain, Wan Nur; Wulandari, Sephia; Jalil, Rifqi (Jurnal Transformasi Global, 2023)
The United Nations (UN) adopted the Convention on the Rights of Persons with Disabilities in late 2006, with the fundamental aim of upholding the human rights interests of persons with disabilities in sustainable development. As of August 2021, the Convention has been ratified by 183 member states of the United Nations (UN), one of them being Japan in early 2014. The ratification of the Convention by Japan was then followed by several amendments to the Japanese Law, which were also followed by initiating policies in the education sector for people with disabilities, one of which is the Special Needs Education program. The implementation of several policies implemented by the Government has led Japan to be ranked 24th among 134 countries in the world with a high global development inclusiveness index. Therefore, this article aims to explain how the Japanese Government's strategy and policy measures in disability education using the approach or concept of inclusive development. The research in this article uses the library research method by using literature such as documents or data that has been published, including journal articles, reports, laws, and regulations from the Japanese Government, related institutions, and international organizations through their official websites. With this, the author's findings presented in this article, namely the existence of policies on Education for people with disabilities in Japan, which in their realization, use the basic principles of inclusive development. Keywords : Policy; Japan's inclusive development; Education for the Disabled; school and curriculum system.